Optimization of Student Executive Body Organization Through Human Resource Performance - Fadqham Dhiwa Nusantara; Laila Nur Aini; Muhammad Fatih Farras; Thohal Fasyni; Ratih Ayu Sekarini (Institute of Advanced Knowledge and Science, 2025)
Universities are very important places in individual development, not only in terms of academics but also in the development of non-academic potential. This must be done so that one does not become a student with minimal knowledge, minimal experience, and minimal skills. Student organizations also serve as a platform for the interests and talents of active students on campus. This research aims to identify the roles of motivation, training, and organizational culture in improving the performance of the Student Executive Board (BEM) of the Faculty of Economics at the Islamic University of Jakarta. A qualitative approach, utilizing interviews and observations with BEM members to gain insights into their motivation, training experiences, and the prevailing organizational culture. The findings indicate that a strong motivational framework, relevant training programs, and a positive organizational culture significantly contribute to the productivity and engagement of BEM members. With a qualitative approach, this research involved 4 subjects who were previously active in the BEM FE, conducting in-depth interviews and using thematic analysis. The research results show that these factors play a crucial role in optimizing the organization of the Student Executive Board (BEM) to achieve the organization's goals efficiently and effectively. Through human resource performance, it shows that motivation, training, and organizational culture play a crucial role in enhancing the performance and effectiveness of the Student Executive Board (BEM) of the Faculty of Economics at the Islamic University of Jakarta. By building strong motivation, providing relevant training, and developing a positive culture, the Student Executive Board (BEM) can function as a significant agent of change for students and the faculty as a whole.